2018
DOI: 10.3390/genes9030171
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Listeria monocytogenes Isolates Associated with Clinical Listeriosis and the Food Production Environment in Ireland

Abstract: Listeria monocytogenes is a major human foodborne pathogen that is prevalent in the natural environment and has a high case fatality rate. Whole genome sequencing (WGS) analysis has emerged as a valuable methodology for the classification of L. monocytogenes isolates and the identification of virulence islands that may influence infectivity. In this study, WGS was used to provide an insight into 25 L. monocytogenes isolates from cases of clinical infection in Ireland between 2013 and 2015. Clinical strains wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
49
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 50 publications
10
49
2
Order By: Relevance
“…The LIPI4 is a newly described Listeria pathogenicity island [56] which encodes for the genes that annotated as a cellobiose family PTS system [55], and it was not identified in any of the strains identified in this study. The LIPI4 appears to be strongly associated with ST4 isolates [1]; hence, it was not observed in the current study. Several studies have identified mutations that are important in L. monocytogenes virulence markers [40,[56][57][58].…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…The LIPI4 is a newly described Listeria pathogenicity island [56] which encodes for the genes that annotated as a cellobiose family PTS system [55], and it was not identified in any of the strains identified in this study. The LIPI4 appears to be strongly associated with ST4 isolates [1]; hence, it was not observed in the current study. Several studies have identified mutations that are important in L. monocytogenes virulence markers [40,[56][57][58].…”
Section: Discussioncontrasting
confidence: 66%
“…LIPI3 is overrepresented among lineage I strains in human isolates and is strongly associated with serotype 4b isolates [55]. The absence of LIPI3 in two samples of lineage II was expected as the sequence types have been reported to lack it LIPI [1]. The LIPI4 is a newly described Listeria pathogenicity island [56] which encodes for the genes that annotated as a cellobiose family PTS system [55], and it was not identified in any of the strains identified in this study.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Overall, the L. monocytogenes population in the UK fresh produce supply chain is diverse, in line with food isolates other countries such as Ireland (Hilliard et al, 2018), France (Moura et al, 2017), and Australia (Kwong et al, 2015). While some isolates have the necessary genomic components to cause disease and are closely related to outbreak strains, others are distantly related and are of less concern.…”
Section: Accepted Manuscriptmentioning
confidence: 99%